2015
DOI: 10.1186/s12938-015-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Web platform using digital image processing and geographic information system tools: a Brazilian case study on dengue

Abstract: BackgroundDengue fever is endemic in Asia, the Americas, the East of the Mediterranean and the Western Pacific. According to the World Health Organization, it is one of the diseases of greatest impact on health, affecting millions of people each year worldwide. A fast detection of increases in populations of the transmitting vector, the Aedes aegypti mosquito, is essential to avoid dengue outbreaks. Unfortunately, in several countries, such as Brazil, the current methods for detecting populations changes and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
5
0
5
Order By: Relevance
“…Its capacity for transmission is due to its rapid adaptation to different environmental contexts. This plasticity is essential for initiating epidemics of major demographic magnitudes, especially in tropical regions (Costa et al , Brasil et al ). In this context, deforestation and urbanization stimulate the synanthropy of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Its capacity for transmission is due to its rapid adaptation to different environmental contexts. This plasticity is essential for initiating epidemics of major demographic magnitudes, especially in tropical regions (Costa et al , Brasil et al ). In this context, deforestation and urbanization stimulate the synanthropy of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Egg counting software has the potential to remove the need for manual counting and improve the accuracy and consistency of subjective rapid visual estimates [68]. We demonstrated that systems developed to count eggs harvested under laboratory conditions [69, 70] may not be suitable for rapid analyses of field collections due to greater exposure of ovistrips to contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…O processo quando realizado desta forma é bastante cansativo e sujeito a falhas, uma vez que demanda muito esforço visual contínuo do responsável. Além disso, como citado por Brasil et al (2015), pode haver ainda variações nas leituras, quando feitas por diferentes profissionais ou quando há sobreposição de ovos.…”
Section: Figura 1: Lâmina De Ovitrampa Contendo Ovos Deunclassified
“…Em geral, uma ovitrampa tem cerca de 12 cm de profundidade com uma abertura circular com 5 cm de raio. Os pesquisadores sugerem ainda a adoção de cerca de 200 ml de líquido por armadilha (Brasil et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation